Some environmental management aspects in loading - unloading and storage of toxic chemicals at seaports in Hai Phong - Quang Ninh - Tuan, Tran Anh; Lan, Tran Dinh; Dinh, Ngo Kim (Vietnam Journal of Marine Science and Technology, 2020)
Toxic chemicals strictly controlled by the International Maritime Organization (IMO) are dangerous goods which can potentially cause environmental degradation in maritime transport. Within the seaports of Hai Phong - Quang Ninh, the volume of toxic chemicals accounted for about 1% of container throughput (over 56 million tons per year, 2017) and many incidents took place during goods loading and unloading at the ports. Although they did not cause significant environmental damages, the prevention of and response to these incidents have revealed many drawbacks. This article presents the identification and assessment of environmental risks and the current status of the prevention of environmental degradation in the loading - unloading and storage of toxic chemicals at seaports in Hai Phong - Quang Ninh.